Foresight and Historical Determinism in Islamic Contemplate - Qader Mohammad Hassan; Nabaz Jalal Jameel (Zanco Journal of Humanity Sciences)
The research reviews the importance of studying foresight and historical determinism in Islamic thought and analyzing its developments in religious and historical contexts, as divine providence and historical determinism constitute fundamental aspects of Islamic thought, and it is believed that history and its development are affected by God’s intervention and the influence of divine factors, as God Almighty is the Creator and Master of everything. And it contributes directly to the course of historical events and human issues. Thus, Islamic thinkers believe that a correct understanding of history requires looking at the divine powers and wisdom behind the events, as well as an acknowledgment of predestination and how they affect the direction of the course of history. The research deals with the profound scientific benefits of this topic in directing... Human thinking towards a better future and drawing lessons from history. The approach followed for this research is to provide comprehensive explanations of forward-looking and deterministic theories, using the historical context as a framework for clarification.